The Implementation of Direct Learning by Using Handout toward Students Achievement in Biology Subject at Class VII-1 of Junior High School Rokan IV Koto in Academic Year 2014/2015 - Syafitri, Listia (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The purpose of this research is to find out the studentsâ achievement in Biology subject at class VII-1 of Junior High School Rokan IV Koto, RokanHulu Regency in academic year of 2014/2015 through the implementation of direct learning by using handout which was conducted in January to July 2015. The design of this research is Classroom Action Research (CAR). The subjects of the research are 24 students including 9 males and 15 females. This research has 2 cycles including 6 meetings at cycle I and 4 meetings at cycle II. Parameter measured is the studentsâ learning achievement in comprehension and mastery which are obtained through quiz in each meeting and block exams in each cycle. Data is analyzed descriptively. The analysis from the implementation of direct learning shows studentsâ comprehension increased by 19,77% before CAR (63,38%), after CAR of cycle I (83,15%), and increased by 4,49% after cycle II (87,64%). Studentsâ mastery before CAR (50%) increased to 83,33% after Cycle I and at cycle II, it increased by 12,5% to be 95,83%. KI score before CAR was 91,66% increasing by 8,34% after cycle I of CAR (100%) and after cycle II (100%). In conclusion, the implementation of direct learning by using handout can improve studentsâ achievement in Biology subject at the Class VII-1 of Junior High SchoolRokan IV Koto in academic year 2014/2015.